Health‐related quality of life in paediatric haemophilia B patients treated with rIX‐FP - von Mackensen, Sylvia; Shah, Jinesh; Seifert, Wilfried; Kenet, Gili (Haemophilia : the official journal of the World Federation of Hemophilia, 2019)
Introduction Frequent infusions and bleeds can impact on the health‐related quality of life (HRQoL) of paediatric haemophilia B patients. rIX‐FP (IDELVION®) is a fusion protein linking recombinant factor IX with recombinant albumin, and is associated with low bleeding rates with a weekly regimen, which could improve HRQoL. Aims To measure the effect of rIX‐FP prophylaxis on the HRQoL of paediatric patients and treatment satisfaction in their caregivers using the Haemo‐QoL and Hemo‐SATP questionnaires, respectively. Methods At baseline and end‐of‐study (EOS), patients 4‐11 years old participating in the PROLONG‐9FP program answered the Haemo‐QoL questionnaire and gave information on their socio‐demographic data and physical activity. Caregivers completed the Hemo‐SatP. Minimal important differences (MID) (|Cohen's d| > 0.5) between baseline and EOS and the number of responders (patients with meaningful subject‐level improvements over time) at EOS were calculated. Results Twenty patients (age group I: 4‐7 years old [n = 12]; age group II: 8‐12 years old [n = 8]) completed the Haemo‐QoL questionnaire at baseline. MIDs were found in age group I representing improvement for “physical health” (d = −0.547) domain; 60% of patients were responders for “physical health.” In age group II, MIDs were seen in most domains; 71.4% patients were responders in “total score.” In caregivers, improvements were seen for most domains of the Hemo‐SatP with a small effect size. Fewer patients missed school when treated with rIX‐FP and 94.1% patients maintained their physical activity level. Conclusion Prophylaxis with rIX‐FP led to substantial improvements in HRQoL in paediatric patients and treatment satisfaction in caregivers.